MEDIAÇÃO MULTIMIDIÁTICA DO CONHECIMENTO: UM REPENSAR DO PROCESSO COMUNICACIONAL DOCENTE NO ENSINO SUPERIOR - Hack, Josias Ricardo (2004)
This dissertation examines the teaching communication process for the multimedia mediation of knowledge. The objective of this research is to point out that the qualification of teachers in Distance Education promotes the development of a new teaching attitude towards Higher Education and that it provides opportunities for reflection and improvement of communication practices through the use of ICT Information and Communication Technologies. In order to reach this objective several theories from the Communication and Education fields, connected to other areas of knowledge, were considered. The research method utilized was the Case Study on the qualification of teachers in Distance Education, proposed by UNOESC University of West Santa Catarina between 2002 and 2004. It is important to note that this study is not an isolated topic since it is embedded in the multimedia mediation of knowledge. The unique contribution of this work is based on the communicational process of the teachers who adopt Distance Education strategies in the Higher Education which was found to be different from that adopted in a face-to-face setting. During this study it was observed that it is necessary to prepare teachers so that they can change their communicational attitude towards Distance Education. In the last chapter of this dissertation a continuing qualification program for teachers through Distance Education is proposed. This program is based on the principles of criticism, creativity and contextualization keeping in mind that the teacher as a learner of multimedia mediation is the focus.